Study protocol: neonatal colonisation and infection with Ureaplasma in very immature preterm infants born <29 weeks of gestation (NEO-CONSCIOUS): a prospective multicentre study assessing early life colonisation rates and potentially associated adverse outcomes - Glaser, Kirsten; Rittenschober-Böhm, Judith; Humberg, Alexander; Stichtenoth, Guido; Butzer, Sarina; Mehler, Katrin; Kipfmüller, Florian; Köstlin-Gille, Natascha; Gille, Christian; Kick, Andrea; Dornis, Diana; Henrich, Birgit; et al. (BMJ open, 2025)
Introduction Preterm infants, particularly those born before 29 weeks of gestation, are at increased risk of developing bronchopulmonary dysplasia (BPD) and other complications of prematurity. Substantial evidence suggests that respiratory tract colonisation with Ureaplasma species significantly contributes to pulmonary inflammation, impaired lung function and subsequent lung disease especially in very immature infants. Moreover, Ureaplasma exposure has been implicated in the pathogenesis of other inflammation-related sequelae of prematurity. Although representing a potentially actionable risk factor for adverse short-term and long-term neonatal outcome, controversies on Ureaplasma-associated morbidity remain and recommendations for screening practices in preterm infants are missing. The NEO-CONSCIOUS (Neonatal Colonisation and Infection with Ureaplasma in very immature preterm infants born <29 weeks of gestation) study aims to assess the incidence of Ureaplasma colonisation and infection in very preterm infants at high risk of adverse outcome, the extent of potentially accompanying inflammation and the impact on short-term and long-term morbidity. - Methods and analysis This is a prospective observational multicentre study being conducted in level III neonatal intensive care units in Germany and Austria. In total, 400 infants born before 29 weeks of gestation are screened for Ureaplasma colonisation immediately after birth. In addition, biomarkers of systemic inflammation are determined on day 1 and day 28. The study infants are followed up until discharge and at 2 years corrected age. The primary outcome BPD and/or death is assessed at 36 weeks postmenstrual age. Secondary outcomes include systemic inflammation, secondary infections, intraventricular haemorrhage, periventricular leukomalacia, necrotising enterocolitis, retinopathy of prematurity and neurodevelopmental outcome at 24 months corrected age. - Ethics and dissemination The study has been approved by the ethics committees in Würzburg and Leipzig and the local ethics committees of all participating centres. Results will be disseminated through peer-reviewed international publications and conferences. The study is registered with the German Clinical Trials Register, ID DRKS00033001. - Trial registration number German Clinical Trials Register (DRKS00033001).
Gesehen am 30.10.2025